On the impact of global interactions on the structure of metallic glasses - Stiehler, Martin E.; Jolly, Mark R.; Georgarakis, Konstantinos (Elsevier, 2018)
The influence of global interactions between the static atomic structure and the valence electrons on structure formation in binary Al-(Ni,Cu,Zr), Zr-(Ni,Cu) and ternary Al-(Ni,Cu)-Zr metallic glasses is investigated over wide concentration ranges and discussed in terms of a Hume-Rothery-like theory by analysing and comparing data available in the literature. The results suggest that global interactions lead to an improvement of thermal stability and glass-forming ability. A complete understanding of structure formation in the considered alloys is assumed to be possible only by taking into account both local and global effects.
Keywords: Aluminum alloys; Zirconium alloys; Metallic glasses; Electronic structure; Glass-forming ability; Hume-Rothery